Pengaruh Penggunaan Mulsa dan Pupuk NPK Terhadap Produktivitas Kacang Hijau (Vigna radiata L.) (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2022)
Mung beans (Vigna radiata L.) are an essential food source supporting the food diversification program. Mulch and fertilization are among some means to increase the productivity of mung beans. A study was aimed to determine the effect of using mulch and NPK fertilizer on the productivity of mung beans. This study employed an environmental design, namely a two-factor Randomized Block Design. The tested factors included straw mulch and the dosage of NPK fertilizer. Mulch consisted of two levels, which were without and with straw mulch. The dosage of NPK fertilizer comprised of three levels, namely 100 gr/plant, 150 gr/plant, and 200 gr/plant. From the two factors, six treatment combinations were obtained with four replications so that there were 24 treatments combination. The result data was analysed by analysis of variance (ANOVA) if the treatment showed a difference, continued with the Least Significant Difference (LSD) test at 5% level. The use of mulch could increase the plant height from 3.39 to 5.17 cm, 4.8% of the number of leaves, 32% of dry seed weight consumption per plant, 3% of wet weight, and 33% of plant dry weight compared to no mulch. The dosage of NPK fertilizer by 150 grams/plant gave the best results on the productivity of mung beans. The use of mulch and NPK fertilizer did not show interaction on the productivity of mung beans. Kacang hijau merupakan sumber penting untuk menunjang program diversifikasi pangan. Peningkatan produktivitas kacang hijau dapat dilakukan melalui pemupukan dan rekayasa lingkungan dengan mulsa. Penelitian bertujuan untuk mempelajari penggunaan mulsa, pupuk NPK dan interaksinya terhadap produktivitas tanaman kacang hijau (Vigna radiata L.). Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok (RAK) dua faktor. Faktor pertama yaitu penggunaan mulsa terdiri atas 2 taraf: tanpa mulsa dan mulsa jerami. Faktor kedua yaitu dosis pupuk NPK terdiri atas 3 taraf: 100 gr/tanaman, 150 gr/tanaman, dan 200 gr/tanaman. Kombinasi perlakuan sebanyak 6 dan pengulangan 4 kali sehingga terdapat 24 kombinasi perlakuan. Data dianalisis menggunakan analysis of variance (ANOVA), apabila perlakuan menunjukkan perbedaan diuji lanjut dengan uji Beda Nyata Terkecil (BNT) taraf 5%. Penggunaan mulsa jerami mampu meningkatkan tinggi tanaman kacang hijau 3.39-5.17 cm, jumlah daun 4.8%, berat biji kering konsumsi per tanaman 32%, berat kering 33% dan berat basah tanaman 3% dibandingkan tanpa mulsa. Pupuk NPK dosis 150 gram/tanaman memberikan hasil terbaik terhadap produkstivitas kacang hijau. Penggunaan mulsa dan pupuk NPK tidak menunjukkan interaksi terhadap produktivitas kacang hijau.